Predictive Accuracy of Full Outline of Unresponsiveness Score and GCS to Predict Patient’s Poor Outcome in Pediatrics ICU - Sehar Zahid, Sadia Qasim, Muhammad Anwar, Syed Abdullah Mazhar, Shahzia Siddique, Arshad Rafique (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the predictive accuracy of Glasgow coma Scale (GCS) versus full outline of unresponsiveness score (FOUR score) for poor out-come prediction in children admitted in paediatric ICU. Study design: Descriptive cross-sectional study. Place and duration of study: Department of Pediatrics, Services Hospital Lahore from 29th June 2017 to 29th December 2017. Methodology: One hundred and seventy children were enrolled. Both GCS and FOUR scale scores were recorded in paediatric intensive care unit (ICU) by clinical examination within 30 minutes of arrival in ICU. Both GCS and FOUR score were calculated on each and every patient. Responses were noted by clinically examining the eye, motor, verbal and brain stem reflexes. Patients were followed upto 7 days and poor outcome was noted. Results: The frequency of pediatric mortality was 52 (30.59%). Predictive accuracy of Full Outline of Unresponsiveness Score (FOUR score) for poor outcome prediction in children admitted in paediatrics ICU showed 63.46% for sensitivity, 86.44% for specificity, 67.35% for PPV, 84.30% for NPV and 79.41% for accuracy rate, whereas predictive accuracy of GCS Score for prediction of poor outcome in children admitted in paediatrics ICU shows 55.76% for sensitivity, 83.89% for specificity, 60.42% for PPV, 81.15% for NPV and 75.29% for accuracy rate. Conclusion: The FOUR and GCS both showed good results in terms of mortality after one week of admission in pediatric ICU. Key words: Children, poor outcome, FOUR score, Glasgow coma scale, predictive accuracy